Tribulus terrestris Fruit Extract: Bioactive Compounds, ADMET Analysis, and Molecular Docking with Penicillin-Binding Protein 2a Transpeptidase of Methicillin-Resistant Staphylococcus epidermidis - Khalid J. Alzahrani (Current Issues in Molecular Biology)
Tribulus terrestris is a rich source of bioactive molecules and thrives in Mediterranean and desert climate regions worldwide. In this study, Tribulus terrestris methanolic HPLC fractions were evaluated for bioactive compounds and PBP2a transpeptidase inhibitors against methicillin-resistant Staphylococcus epidermidis (MRSE). Among the collected HPLC fractions, F02 of the methanol extract demonstrated potential activity against MRSE01 (15 ± 0.13 mm), MRSE02 (13 ± 0.21 mm), and MRSE03 (16 ± 0.14 mm) isolates. GC-MS analysis of the F02 fraction identified seventeen compounds. Among seventeen compounds, eight have favorable pharmacokinetics and medicinal chemistry; however, on the basis of in silico high water solubility, high GI absorption, blood–brain barrier non-permeability, lack of toxicity, and potential drug-likeness, 1-ethylsulfanylmethyl-2,8,9-trioxa-5-aza-1-sila-bicyclo[3.3.3]undecane and phthalimide, N-(1-hydroxy-2-propyl), were processed for molecular docking. 1-ethylsulfanylmethyl-2,8,9-trioxa-5-aza-1-sila-bicyclo[3.3.3]undecane formed three hydrogen bonds with Ser-452, Thr-584, and Asn-454 residues of the PBP2a transpeptidase. Similarly, phthalimide, N-(1-hydroxy-2-propyl)-formed four hydrogen bonds with Ser-396, Asn-454, Lys-399, and Ser-452 residues of PBP2a transpeptidase. These two compounds are proposed as novel putative PBP2a transpeptidase inhibitors. Further characterization of compounds extracted from Tribulus terrestris may aid in identifying novel PBP2a inhibitory agents for managing MRSE infections.